(untitled) (Research, Society and Development, 2025)
Objective: The objective of this literature review is to evaluate the benefits of hydrotherapy in reducing pain and improving the quality of life of women with fibromyalgia. Methodology: A search for articles was conducted in the electronic databases PubMed, PEDro, Google Scholar, and SciELO, covering the period from 2013 to 2023 and indexed in Portuguese and English. Articles that included randomized and prospective clinical trials were selected. Results: The analyzed articles indicate that hydrotherapy, with protocols including warming up, stretching, muscle strengthening, and relaxation, offers greater benefits in reducing pain, improving functional capacity, and reducing muscle fatigue compared to exercises performed on land. Additionally, studies addressing educational programs about fibromyalgia also reported similar benefits. Conclusion: Aquatic physiotherapy offers significant benefits for women with fibromyalgia, mainly in reducing pain, improving functional capacity, and enhancing quality of life.